Tailoring the heterojunction of TiO2 with multivalence CeO2 nanocrystals - for detection of toxic 2-aminophenol. (July 2022) - Manoj, Devaraj; Rajendran, Saravanan; Vasseghian, Yasser; Ansar, Sabah; Gracia, F.; Soto-Moscoso, Matias
Abstract: Enhancing the current signal response for semiconductors is the key factor for designing and fabrication of efficient electrode in electrochemical sensors. By the aid of doping with binary metal oxides, the conductivity of the resultant titanium oxide (TiO2 ) based nanocomposite will deliver fast electron transfer rate at the heterojunction interface. Herein, by taking advantage of mesoporous structure in TiO2, cubic shaped multivalent cerium oxide (CeO2 ) was incorporated into the porous cavity by simple ground assisted solvothermal process, which resulted in enormous enhancement in the current response towards detection of 2-aminophenol. The advantage of CeO2 on TiO2 not only involves the loading of binary metal oxide on its mesoporous sites, but also facilitates the formation of CeO2 nanocrystals which induce larger surface area and high electroactive sites with rapid diffusion of target species through pores. As a result, CeO2 –TiO2 on modified GC electrode exhibits drastic enhancement in the current response for oxidation of 2-aminophenol with large decrease in the onset potential than TiO2 /GC electrode. Furthermore, the CeO2 –TiO2 modified electrode shows significant behavior for sensing of 2-aminophenol with wide linear range of 0.01–500 μM. The sensitivity and detection limit were calculated to be 0.603 μA μM cm −2 and 3.5 nM respectively. This work establishes the facile strategy for decoration of binary metal oxide-based nanocomposites as effective electrode and also possible to create new opportunities in the designing and fabrication of variety of efficient electrode in various electrochemical applications.